Evaluation on indoor thermal comfort improvement of Baffle Natural Ventilation System for rural overhead building in Hot-summer and Cold-winter zone - HAIQIANG LIU (International Association of Lowland Technology, 2020)
The rapid growth in urbanization and economy activities has led to an increase in energy consumption, which hastens the depletion of available energy resources and causing the traditional villages to lose regional characteristics in China. The building sector is one of the major end-users of energy. And On the other hand, the air conditioning system is viewed as an important tool to sustain and improve the thermal comfort of occupants （Thermal comfort assessment and potential for energy efficiency enhancement in modern tropical buildings: A review）, that seriously enhanced the energy and environment risks, especially in Hot-Summer and Cold-Winter (HSCW) zone. Therefore, it is vital to find a green and sustainable way to construct. The problems of rural public buildings in Hot-summer and Cold-winter Zone were analyzed and summarized. The rural overhead public building which authors involved in was selected to be the research object, as its’ avoid hardening of the land and reducing the heat island effect. In combination with the local climate, passive natural ventilation technology, like Baffle Natural Ventilation System, was applied in the overhead layer. Combined with the Venturi effect, the natural wind channel is formed to realize the effect of wind guidance, especially in the mid-season in the HSCW zone. In order to evaluate the Baffle Natural Ventilation System’s impact on the overhead buildings’ indoor thermal comfort, field survey study and simulation were carried out in rural public building of Tonglu town in the HSCW zone in China. Also, PPD-PMV was calculated to evaluate the thermal comfort improvement of the baffle natural ventilation system for a rural overhead building in the HSCW zone. Finally, the method of construction with good climate adaptability was proposed, which provided a reference for a rural intensive construction.